Relationships between attitudes toward money and materialism in the consumer society: a study with preadolescents (Práxis Educativa, 2025)
This investigation is grounded in economic psychology, with its findings articulated in dialogue with Zygmunt Bauman’s thought. It problematizes consumerism as a hegemonic social logic and highlights education as a space for developing resistance to the dynamics that turn young people into commodities.  With the aim of examining the relationship between attitudes toward money and materialism in preadolescents, the study included 195 students aged between 10 and 15 years. A materialism scale and a scale of attitudes toward money were used. Data were analyzed through correlation and linear regression. Attitudes toward money served as indicators of materialistic values, pointing to socialization processes typical of liquid modernity, marked by fragile bonds, fluid identities, and the transformation of individuals into consumers even before they reach adolescence.Keywords: Socioeconomic status. Gender. Consumption.